(untitled) (Journal of Applied Learning and Teaching, 2022)
Effective online interaction is beyond interacting with whomever. The quality of social interconnectivity matters. Social presence plays a vital role in building an effective online learning community. This study empirically examined: how online social presence will predict various aspects of students’ social interconnectivities (i.e., in-degree, out-degree, betweenness centrality, closeness centrality, eigenvector centrality, reciprocated vertex pair ratio, & PageRank) in the social network of discussion board within an online course? The predictive utility of social presence for all social network interconnectivity was supported, but reciprocated vertex pair ratio, so-called two-way interconnectivity was not. Social presence serves as a strong predictor for social interaction and interconnectivity. Learners with higher social presence are more likely to play distinguished roles of influencer, liaison, transmitter, social strategist, and prestigious figure of a community of learners. The findings would support online instructors to facilitate, guide, and support their students to navigate through the convoluted social interconnectivity effectively and continuously.